The Effect of Backrest Roller on Warp Tension in Modern Loom - Ahmed, Toufique; Sowrov, Kazi; Alam, Shaikh Md. Mominul (European Scientific Journal, ESJ, 2017)
The Backrest roller is one of the key parts of the weaving machine. In this study, the effect of the various position of backrest and dropper has been assessed. The tension is measured by using the integrated tension measuring device of the loom. The tension can be found on the display board. The effect of backrest position can be described in two different ways viz. keeping constant dropper position (distance between dropper line and backrest roller) and keeping constant dropper depth (distance between held frame and dropper line). If dropper position (distance between backrest roller to dropper line) is kept constant then the backward movement of backrest roller will entail low tension. The reason behind this is, the dropper weight will be moved toward the backrest roller and will lose its influence on warp tension. But if dropper depth is kept constant (i,e dropper line is kept intact) then the backward movement of backrest will require more tension as the influence of dropper will more on warp length. On the other hand, when backrest height is lowered then, the downward movement of backrest roller will need low tension and upward movement of backrest roller will need more tension. As the warp length and lap angle increases with the backrest height. In this paper, the whole phenomenon is explained with illustration.